THE IMPACT OF KNOWLEDGE, ATTITUDE AND PRACTICE OF EATING BEHAVIOR ON STUNTING AND UNDERNUTRITION IN CHILDREN IN THE AGRICULTURAL AREA OF JEMBER DISTRICT, INDONESIA - Ancah Caesarina Novi Marchianti; Dwita Aryadina Rachmawati; Ida Srisurani Wiji Astuti; Angga Mardro Raharjo; Rony Prasetyo (Jurnal Berkala Epidemiologi, 2022)
Background: Indonesia as an agricultural country is still having nutritional problems (stunting and undernutrition) caused by mothers’ lack of knowledge, attitude and practice of eating behavior. Purpose: This research aims to investigate the impact of knowledge, attitude, and practice of eating behavior of mothers of children under five on stunting and undernutrition prevalence in the agricultural communities in Jember. Methods: This cross-sectional research used questionnaires as a method to collect data from respondents i.e. mothers who have toddlers about the knowledge, attitudes and practice of eating behavior. The research was conducted in 2018-2019 in Jember. A total of 414 respondents who met the inclusion criteria (those resided in the study area and were willing to participate in this study) were chosen through random sampling. The data were then analyzed by using Spearman rho’s test to search the effect of the knowledge and attitudes of the mothers of under fives toward stunting and undernutrition. While eating behavior was described based on the results of interviews with respondents on 2x24 hours of food recall and food frequency questionnaires.  Results: This study showed that knowledge and attitudes of mothers regarding eating behavior were related to the occurrence of stunting (p = 0.01; p = 0.04) and malnutrition (p = 0.04), except for the attitude variable towards malnutrition (p = 0.81). Data analysis results regarding eating behavior showed that there was still a lack of fulfillment of certain nutrients, both macronutrients (fiber) and micronutrients (Vitamin B1, Vitamin C, Vitamin E, Potassium, Sodium, Calcium and Folic Acid.) to the RDA reference which was recorded as severe deficiency in 60-97% of children under five. Conclusion: Adequate knowledge and attitudes of mothers of diet can be a factor that prevents nutritional problems (stunting and malnutrition). The consumption pattern assessed showed that there was still a lack of fulfillment of certain nutrients both macro (fiber) and micronutrients against RDA reference. Further research needs to be done to explore the right promotive and prevention approach based on the lack of nutrition found in each area.